2019
DOI: 10.1021/acs.iecr.9b01643
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of Aliphatic Dicarboxylic Acids in Wet Air Oxidation Conditions

Abstract: The reactivity of the aliphatic dicarboxylic acids (DCAs) mixtures in conditions similar to industrial wet air oxidation (WAO) process conditions has been investigated. DCAs have potential to be separated during WAO of highly polymerized organic matter (e.g., organic waste, biomass, kerogen in oil shale) before transforming to final oxidation products (CO 2 and water). However, a shortage of information about the DCAs stability in such processes restricts this application. The influence of oxygen pressure, tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 50 publications
(113 reference statements)
0
6
0
Order By: Relevance
“…This indicates that the temperature rise caused faster degradation of the primary oxygenated intermediates. A similar phenomenon was described in our previous work for DCA stability, where we found that at 200 °C, a considerable degradation of DCAs (C4–C10) occured . When the WAO of the oil shale was carried out at lower temperatures, ranging from 150 to 165 °C, the yield of the formed DCAs was less than 6%.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…This indicates that the temperature rise caused faster degradation of the primary oxygenated intermediates. A similar phenomenon was described in our previous work for DCA stability, where we found that at 200 °C, a considerable degradation of DCAs (C4–C10) occured . When the WAO of the oil shale was carried out at lower temperatures, ranging from 150 to 165 °C, the yield of the formed DCAs was less than 6%.…”
Section: Resultsmentioning
confidence: 73%
“…A similar phenomenon was described in our previous work for DCA stability, where we found that at 200 °C, a considerable degradation of DCAs (C4–C10) occured. 33 When the WAO of the oil shale was carried out at lower temperatures, ranging from 150 to 165 °C, the yield of the formed DCAs was less than 6%. In this respect, the temperature range for the acceptable conversion of the oil shale to SO and the formation of DCAs is around 175 °C.…”
Section: Resultsmentioning
confidence: 99%
“…For K-70 and K-90, the amount of C6-C10 DCAs was 14% and 7%, respectively [24]. It has also been demonstrated that pure DCAs are relatively stable in water up to 175 °C or higher, but the presence of bases or organic co-oxidants induces their decomposition [32]. Therefore, the decomposition of the formed products is an essential factor when adapting the WAO process to oil shale to obtain DCA.…”
Section: Dca Destruction In the Presence Of Oil Shalementioning
confidence: 99%
“…This treatment offers a high versatility and efficiency in the degradation of different nonbiodegradable organic pollutants, using air or oxygen gas as oxidants under moderate to high temperature (below 200 °C) and pressure (5–50 bar) conditions. , Furthermore, the catalytic process (CWAO) improves the degradation of the pollutant, being able to operate at milder conditions in a real-scale scenario . Generally, the pollutants are totally oxidized to carbon dioxide, water, short-chain organic acids, and nonhazardous compounds to the environment …”
Section: Introductionmentioning
confidence: 99%
“…26 Generally, the pollutants are totally oxidized to carbon dioxide, water, short-chain organic acids, and nonhazardous compounds to the environment. 27 The main challenge in the development of a catalyst is to provide a high resistance to the deactivation within the catalytic oxidative process. Generally, supported catalysts based on noble metals such as palladium, platinum, ruthenium, rhodium, etc.…”
Section: Introductionmentioning
confidence: 99%